2019
DOI: 10.1088/1367-2630/ab193d
|View full text |Cite
|
Sign up to set email alerts
|

Generation of arbitrary all-photonic graph states from quantum emitters

Abstract: We present protocols to generate arbitrary photonic graph states from quantum emitters that are in principle deterministic. We focus primarily on two-dimensional cluster states of arbitrary size due to their importance for measurement-based quantum computing. Our protocols for these and many other types of two-dimensional graph states require a linear array of emitters in which each emitter can be controllably pumped, rotated about certain axes, and entangled with its nearest neighbors. We show that an error o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 85 publications
1
42
0
Order By: Relevance
“…Given that arbitrary graph states can be generated solely with Clifford gates 41,42 , which were also exclusively used in the protocols of refs. 24,25,[27][28][29][30][31]36 , restricting ourselves to this set does not affect the generality of our approach. Clifford gates enable the use of the stabilizer formalism, such that we can manipulate Pauli operators instead of keeping track of the whole state.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that arbitrary graph states can be generated solely with Clifford gates 41,42 , which were also exclusively used in the protocols of refs. 24,25,[27][28][29][30][31]36 , restricting ourselves to this set does not affect the generality of our approach. Clifford gates enable the use of the stabilizer formalism, such that we can manipulate Pauli operators instead of keeping track of the whole state.…”
Section: Resultsmentioning
confidence: 99%
“…This idea was extended further to develop protocols that deterministically generate resource states for quantum repeaters [29][30][31][32] -tailored to color centers in refs. 33,34 -and one-way computing 35,36 . References 32,35 allowed for the re-interference of photons with emitters to further enhance flexibility in entanglement creation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2010, Economou et al extended this Lindner-Rudolph scheme by using multiple coupled spin-photon interfaces to create a multidimensional cluster state [28], necessary for quantum information processing [29]. This proposal has since been extended to leverage more recent experimental advances on interactions between QDs [30], and to produce arbitrary graph states from linear arrays of spin-photon interfaces [31].…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [42,43] built on this protocol and demonstrated that entanglement between emitters can be harnessed for the generation of more complex photonic graph states. These ideas have been extended further to general prescriptions and to protocols tailored to specific physical systems [44][45][46][47].…”
mentioning
confidence: 99%